PLESIOSAURS - Moening, Kate; Edwards, Mat; Rathburn, Betsy; Kollock, Jeffrey (Minneapolis, MN : Bellwether Media, Inc., 2023)
"Plesiosaurs lived more than 200 million years ago! What were their lives like as they swam through the world's ancient oceans? This hi/lo title explores that question through leveled text and colorful illustrations. Readers will learn about Plesiosaurs' body parts, favorite foods, behaviors, and more. Features map the prehistoric world, compare Plesiosaurs' sizes, show off favorite foods, and more"--Publisher's website.
Includes index
Bibliography: page 23
Ages 7-12
Grades 4-6
Keywords: Extinct reptiles -- United States -- Juvenile literature; Plesiosaurs -- Juvenile literature; Marine reptiles, Fossil -- Juvenile literature